Defect and pyridinic nitrogen engineering of carbon-based metal-free nanomaterial toward oxygen reduction - Zhang, Jian (2020)
Defect and N-activated electronic engineering are of paramount importance for developing highly active carbon-based electrocatalysts toward oxygen reduction reaction (ORR) because the binding affinity of the carbon matrix can be efficiently tuned and thus promote the electrocatalytic activity. Herein, we present a facile and general strategy for fabricating pyridinic-N dominated and defect-enriched graphene-like nanocarbon material (ND-GLC) involving in-situ alkaline activation of cellulose and ammonia injection. The ND-GLC material has a superior and enhanced ORR activity and stability compared to commercial Pt/C catalyst in both rotating disk electrode measurements and Zn-air battery applications. Experimental and theoretical studies describe that the high electrocatalytic activity of ND-GLC mainly originates from the synergetic effect of edges/defects and pyridinic-N dopants. Importantly, our concept is demonstrated to be universal for other carbon-based nanomaterials (i.e., graphite nanoplates, carbon nanotubes, carbon nanospheres, graphene nanosheets).